(untitled) (Bangladesh Rice Journal, 2015)
Use of marginal coastal saline lands for rice cultivation is one of the options to sustain the net rice cropped area and rice production. On-farm farmers participatory field trial was conducted in Bangladesh during 2012 and 2013 in non-gher and gher of medium saline ecosystems. The objective of the study was to identify suitable Boro variety for medium saline soils. Salt tolerant rice varieties, BRRI dhan47 and Binadhan-8 were evaluated along with widely adopted BRRI dhan28 in non-gher area. BRRI dha47, Binadhan-8 and Binadhan-10 were tested in saline ghers. Crops were irrigated with water of 1.89 to 3.5 dS m-1 at different growth stages respectively. In saline non-gher, where soil salinity went up to 6.35 dS m-1, the highest grain yield was produced by Binadhan-8 (4.57 t ha-1) followed by BRRI dhan28 (4.23 t ha-1). The highest grain yield was recorded in Binadhan-10 (5.14 t ha-1) in ghers which was 6 and 12% higher than BRRI dhan47 and Binadhan-8 respectively at soil salinity of 7.43 dS m-1. Farmers preferred Binadhan-10 as a salt tolerant variety for its higher grain yield and medium grain quality. Bangladesh Rice j. 2014, 18(1&2): 18-23